Field-based aflatoxin sampling and testing protocol - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Field-based testing was conducted as part of farmer-managed Aflasafe BF01 maize and groundnut demonstration plots across 10 sites in Burkina Faso.The promising results of the field-based tests compared to the lab-based tests were shared with the partnering farmer organisations and companies. More demonstrations are planned as the protocol is refined.